2011
DOI: 10.1111/j.1471-4159.2011.07510.x
|View full text |Cite
|
Sign up to set email alerts
|

Are amyloid‐degrading enzymes viable therapeutic targets in Alzheimer’s disease?

Abstract: J. Neurochem. (2012) 120 (Suppl. 1), 167–185. Abstract The amyloid cascade hypothesis of Alzheimer’s disease envisages that the initial elevation of amyloid β‐peptide (Aβ) levels, especially of Aβ1‐42, is the primary trigger for the neuronal cell death specific to onset of Alzheimer’s disease. There is now substantial evidence that brain amyloid levels are manipulable because of a dynamic equilibrium between their synthesis from the amyloid precursor protein and their removal by amyloid‐degrading enzymes (ADEs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
198
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 214 publications
(205 citation statements)
references
References 219 publications
(418 reference statements)
5
198
0
2
Order By: Relevance
“…A is physiologically derived from  and  cleavage of APP and degraded by a number of enzymes [79] , although the normal function of A remains still not well understood. A accumulates when the balance between its production and clearance is broken, and FAD-linked mutations of APP and presenilins could enhance A production and lead to early onset AD, suggesting that A overproduction is able to induce the disease onset.…”
Section: Resultsmentioning
confidence: 99%
“…A is physiologically derived from  and  cleavage of APP and degraded by a number of enzymes [79] , although the normal function of A remains still not well understood. A accumulates when the balance between its production and clearance is broken, and FAD-linked mutations of APP and presenilins could enhance A production and lead to early onset AD, suggesting that A overproduction is able to induce the disease onset.…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon will be discussed in detail under the section on suppression of amyloid beta by retinoic acid (4.3). Glutathione suppression is widely seen in degeneration of dopaminergic neurons in PD (Nalivaeva et al, 2012a) and SOD suppression is a common phenomenon in AD (Lee et al, 2009 ). Therefore, retinoic acid could be used as a promising therapeutic drug for most abundant neurodegenerative diseases.…”
Section: Retinoic Acids In Removing Oxidative Stressmentioning
confidence: 99%
“…Amyloid β is a small peptide which has a direct connection with neuro degeneration and it is a well-studied oligomer in neurodegenerative diseases (Nalivaeva et al, 2012a;Miners et al, 2011;Nalivaeva et al, 2008;Nalivaeva et al, 2012b;Koryakina et al, 2009;Morishima et al, 2001) even though few good functions of Aβ have been identified such as synaptic transmission (Turner et al, 2003). Elevated amounts of Aβ can result in pathogenic situations (Nalivaeva et al, 2012b;Koryakina et al, 2009;Morishima et al, 2001).…”
Section: Suppression Of Amyloid Beta By Retinoic Acidmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be due to the mutations of presenelin genes, which provoke the overproduction of Amyloid from amyloid precursor protein (Hardy, 2004). In late-onset Alzheimer's disease, which constitutes more than 90% of the disease, the excess accumulation of Amyloid has been associated with abnormal Amyloid degrading proteases (Nalivaeva et al, 2008). Women are more likely to develop Alzheimer's disease after adjusting for age (Andersen et al, 1999).…”
Section: Introductionmentioning
confidence: 99%